A NEW SPECIES OF HYPOESTES FROM THE ANDAMAN ISLANDS - THOTHATHRI, K. (Research Center for Biology, 1965)
Affinis H. purpureae (L.) Soland. ex Roem. & Schult. a qua tamen differt inflorescentia, forma bractearum involucri atque magnitudine capsularum.